Deformation and phase transformation behaviors of a high Nb-containing TiAl alloy compressed at intermediate temperatures. (10th March 2022) - Liu, Xu; Song, Lin; Stark, Andreas; Lorenz, Uwe; He, Zhanbing; Lin, Junpin; Pyczak, Florian; Zhang, Tiebang
Highlights: The βo (ωo ) phases precipitate within the equiaxed α2 phase during deformation. The ωo phase forms in the lamellae and undergoes further deformation. The precipitation of the βo phase is suppressed by DRX. Abstract: In modern β-solidified TiAl alloys, the decomposition of α2 phase is frequently observed during heat treatment or high-temperature deformation of the alloys. In this study, high-temperature deformation and decomposition mechanisms of α2 phase in a Ti-45Al-8.5Nb-0.2B-0.2W-0.02Y alloy are investigated. In a sample deformed at 800 °C, the precipitation of βo (ωo ) phase is observed within the equiaxed α2 phase. The nucleation of ωo particles within the βo matrix indicates the α2 →βo →ωo transformation. In addition, numerous γ phase precipitates form within the βo (ω) areas. The α2 lamellae decompose into ultrafine (α2 +γ) lamellae and coarsened γ lamellae via α2 →α2 +γ and α2 →γ transformation, respectively. Moreover, the ωo phase nucleates within the ultrafine lamellae via α2 →ωo transformation. However, in a sample deformed at 1000 °C, the nucleation of βo particles is sluggish, which is caused by the efficient release of the internal stress via dynamic recrystallization (DRX). These results indicate that complex phase transformations can be introduced by the decomposition of α2 phase in TiAl alloys with a high amount of β-stabilizing elements.